PENGARUH PEMBERIAN SARI PATI BENGKUANG (Pachyrhizus Erosus) TERHADAP KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELLITUS TIPE II USIA 40-50 TAHUN DI KELURAHAN BANGKINANG WILAYAH KERJA PUSKESMAS BANGKINANG KOTA TAHUN 2018 - Yenny Safitri (Universitas Pahlawan, 2018)
Currently Indonesia is in a period of epidemiological transition. One party still has many infectious diseases on the other hand, the increasing number of non-communicable diseases, one of them is diabetes mellitus. Diabetes mellitus occurs a lot in> 40 years of age. The treatment can use complementary therapies by utilizing yam starch extract. The purpose of this study was to determine the effect of yam starch extract on blood glucose levels of type II diabetes mellitus patients. This study uses a quasi-experimental research design with non randomized control group pretest posttest design. The population in this study were 26 people with type II diabetes mellitus in Bangkinang City. The samples used in this study were 20 people, 10 people as a case group and 10 people as a control group. Sampling using purposive sampling technique. Results of data analysis using univariate and bivariate analysis. The results of the analysis showed that the average blood glucose level of the case group before being given jasmine starch extract was 259.90 mg / dl and after giving 185.40 mg / dl and the control group before blood glucose levels was 238.60 mg / dl and after 249.20 mg / dl. Based on the Mann Whitney U test showed that there were differences in blood glucose levels in the case group with the administration of yam and starch control group with a value of P value = 0.003, a <0.005. So Ha is accepted. It was suggested to the respondents to make the juice of the yam starch as a drink to control blood glucose levels, and to maintain their diet and exercise regularly